2014
DOI: 10.1371/journal.pone.0090653
|View full text |Cite
|
Sign up to set email alerts
|

Where Taxonomy Based on Subtle Morphological Differences Is Perfectly Mirrored by Huge Genetic Distances: DNA Barcoding in Protura (Hexapoda)

Abstract: BackgroundProtura is a group of tiny, primarily wingless hexapods living in soil habitats. Presently about 800 valid species are known. Diagnostic characters are very inconspicuous and difficult to recognize. Therefore taxonomic work constitutes an extraordinary challenge which requires special skills and experience. Aim of the present pilot project was to examine if DNA barcoding can be a useful additional approach for delimiting and determining proturan species.Methodology and Principal FindingsThe study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…However, the intraspecific genetic distances of Paracerella sinensis sp. n. are very high (up to 12.54%), which is in accord with the previous studies on some other proturan species: up to 21.3% in eight individuals of Ionescuellum haybachae from two Austria populations (Resch et al 2014), and up to 31.98% separating 21 representatives of Acerentomon italicum in three Italian populations from an Austrian population (Galli et al 2015). The similar situation was also found in another basal hexapod group–Collembola: six collembolan species sampled from various locations worldwide with high intraspecific variation for COI from 11.33% to 21.47% (Porco et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…However, the intraspecific genetic distances of Paracerella sinensis sp. n. are very high (up to 12.54%), which is in accord with the previous studies on some other proturan species: up to 21.3% in eight individuals of Ionescuellum haybachae from two Austria populations (Resch et al 2014), and up to 31.98% separating 21 representatives of Acerentomon italicum in three Italian populations from an Austrian population (Galli et al 2015). The similar situation was also found in another basal hexapod group–Collembola: six collembolan species sampled from various locations worldwide with high intraspecific variation for COI from 11.33% to 21.47% (Porco et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Animal groups with limited morphological structures, such as the Lampetra genus, that possesses so few of the morphological characters (Mateus et al 2013) or Protura where the taxonomy is based on subtle morphological differences, routine sequence data or even barcoding represent valuable source of information and mirrored by significant genetic distances (Resh et al 2014). The population-genetic studies have been rather productive in the last decades based on the invention of polymerase chain reaction technology and on applying mitochondrial and nuclear neutral markers.…”
Section: Why Neutral Mtdna Marker Is Blind?mentioning
confidence: 99%
“…The geological substratum has been recorded only in a (Table V). Analysing them together with the sequence from a population in Vienna (Resch et al 2014) revealed big distances separating the Italian from the Austrian populations of Acerentomon italicum (maximum intraspecific pairwise distance: 31.98%).…”
Section: Ecologymentioning
confidence: 99%